Impact of fast-track surgery on postoperative complications and patient satisfaction among diabetic patients undergoing elective surgery: a quasi-experimental study - Made Suandika; Rahmaya Nova Handayani; Yuniar Melissa Kisdyanti; Kevin Virirey Mondawitu; The Ayodhya Santam Budjana (Riset Informasi Kesehatan, 2026)
Background: Fast-Track Surgery (FTS) aims to optimise surgical recovery through multimodal interventions that reduce physiological stress and improve patient outcomes. However, its effectiveness among diabetic surgical patients remains underexplored, particularly regarding postoperative complications and satisfaction. Method: This quasi-experimental study compared 30 diabetic patients managed under an FTS protocol with 30 patients receiving conventional perioperative care at a tertiary hospital. FTS interventions included carbohydrate loading, early mobilisation, opioid-sparing analgesia, and structured discharge criteria. Outcomes assessed were postoperative complications and patient satisfaction, analysed using Chi-square and Mann–Whitney U tests. Results: The FTS group demonstrated fewer postoperative complications (20.0%) than the conventional group (46.7%, p = 0.015). Wound infection, transient hyperglycaemia, and thromboembolism were the most frequent events. Patient satisfaction was significantly higher in the FTS group (mean score 4.5 ± 0.6) compared to the conventional group (3.8 ± 0.7, p = 0.023). Multivariate analysis indicated FTS independently reduced complication risk (OR = 0.31, 95% CI: 0.10–0.89, p = 0.031). Conclusion: FTS effectively reduces postoperative complications and enhances satisfaction among diabetic patients undergoing elective surgery. Although limited by its non-randomised design and small sample size, this study highlights the potential of structured perioperative care for high-risk metabolic populations.